The other half of Augusta Hope - Glen, Joanna (The Borough Press, 2019)
Augusta Hope has never felt like she fits in. And she's right. And now that she's an adult, Augusta has no interest in the goings-on of the small town where she lives with her parents and her beloved twin sister, Julia. When an unspeakable tragedy upends everything in Augusta's life, she's propelled headfirst into the unknown. On the other side of the world, a young boy called Parfait is growing up amongst civil war and poverty and dreaming of a better life for himself and his family. Augusta and Parfait will both suffer unimaginable tragedies as they search for a place to be themselves and finally call home.--